Atomic-scale chemical mapping of copper dopants in Bi2Te2.7Se0.3 thermoelectric alloy. (March 2021) - Kim, Y.-M.; Lee, K.H.; Fu, L.; Oh, M.-W.; Yang, S.-H.; Ning, S.; Han, G.; Kim, M.Y.; Kim, J.-S.; Jeong, M.; Jang, J.; Lee, E.; et al.
Abstract: Elemental doping is a universal strategy in controlling the functionalities of materials that strongly correlate with naturally formed atomic defects. Element-resolved chemical mapping for atomic defects has answered numerous problems on the relations between defective structures and properties. However, tracking small amounts of dopants in multicomponent bulks and clarifying their doping behaviors remain challenging. Using advanced X-ray spectroscopy, the excess Cu doping behavior in ternary Bi2 Te2·7 Se0.3 bulk alloy is visualized with the unprecedented detectability from sub-one atomic percent of concentration. The low content of 0.2 at.% Cu preferentially occupies the Bi site, while Cu atoms are found in three crystallographic sites of Bi2 Te3 structure and van der Waals gap at high Cu content of 1.2 at.%. These behaviors explain the nontrivial role of Cu dopants on carrier generation processes and relevant thermoelectric properties of Bi2 Te2·7 Se0.3 . The atomic-level identification should also stimulate the elucidation of diverse properties in doped nanomaterials and quantum phenomena in doped topological insulators. Graphical abstract: Image 1 Highlights: Sub-atomic percent-level dopants in multicomponent semiconductor alloys can be mapped out on the atomic scale. Atomic site-specific doping behavior of Cu in Bi2 Te2·7 Se0.3 semiconductor alloys were comprehensively revealed. The correlation of the doping behavior with the resultant properties was fully elucidated in the entire doping regime. Our STEM-EDX spectrum imaging with a 1 Å-level drift stability facilitates atomic-level elemental mapping.